A drug safety evaluation of rituximab and risk of hepatitis B. (July 2014) - Riedell, Peter; Carson, Kenneth R
Abstract : Introduction: Rituximab is a widely prescribed anti-CD20 mAb for the treatment of CD20 + B-cell non-Hodgkin Lymphoma and many other immune mediated conditions. There is a well-described association between rituximab containing chemo-immunotherapy treatment and reactivation of the hepatitis B virus (HBV). This review summarizes the current literature surrounding rituximab-associated HBV reactivation. Areas covered: Herein, we review the literature detailing the risk of HBV reactivation in inactive carriers and those with resolved hepatitis. The clinical presentation and management of HBV reactivation are also discussed along with a summary of clinical trials evaluating antiviral prophylaxis. Finally, clinical recommendations are detailed. Data from clinical trials, observational studies, reviews, and meta-analyses available in the Medline database were included in this narrative review. Expert opinion: Screening should be performed in all patients prior to the administration of any type of anti-CD20 mAb therapy. Among those with positive screening serology, testing for hepatitis B e antigen or viral load by polymerase chain reaction is appropriate. In those patients with detectable HBV DNA, the decision regarding the use of antiviral prophylaxis or observation should be individualized.